Potentiometric determination of mebeverine hydrochloride antispasmodic drug based on molecular docking with different ionophores host–guest inclusion as a theoretical study. Issue 2 (4th January 2023) - Abdel-Raoof, Ahmed M.; Fouad, Manal M.; Rashed, Noha S.; Hosni, Noha Y. Z.; Elsonbaty, Ahmed; Abdel-Fattah, Ashraf
Abstract : A novel ion selective sensor for detecting MBV in pharmaceutical formulations has been fabricated supported by computational molecular modeling methods. Abstract : The scientific community has continued to pay particular attention to potentiometric sensors based on ion-selective membrane sensors as an energy-efficient, easy-to-use method suitable for microfabrication. To this end, potentiometric ion-selective sensors were used as an alternative green analytical instrument. Three distinct sensors relying on various ionophores were built and assessed. A cationic exchanger, tetra phenyl borate, was used in the polyvinyl chloride polymeric plasticized matrix using di octyl phthalate, where α, β, and γ cyclodextrins were utilized as ionophores. A comparative potentiometric analysis was carried out using three ion-selective sensor designs: α, β, and γ cyclodextrins sensors. β-Cyclodextrin significantly reduced the detection limit and improved the discriminative performance of mebeverine hydrochloride (MBV) in the pharmaceutical dosage form over α- and γ-cyclodextrins in the presence of other interfering chemicals. Additionally, a significant connection was made between the practical perspective and a theoretical investigation based on computational research. Nernstian potentiometric results for the optimum sensor were obtained for MBV in the range of concentrations 1.0 × 10 −2 to 1.0 × 10 −6 M, its slope was −58.70 ± 0.12 mV per decade with lower detection limits 4.50 × 10 −7 M. This computational molecular docking investigation clarified that the binding sites and modes were in good agreement with the experiment results. This investigation was applied to expect the interaction between MBV and the proposed sensors to ensure which ionophores were the best for MBV.